The chemical synthesis of porphobilinogen an important intermediate of the biosynthesis of the "pigments of life" - Bobal, Pavel; Neier, Reinhard (My University, 1997)
Porphobilinogen is the second dedicated intermediate in the biosynthesis of «pigments of life». Only very few alkylpyrroles have been isolated from natural sources so far. The absence of stabilising substituents confers to porphobilinogen a high reactivity. The chemical synthesis of porphobilinogen had to take its sensitivity into account. The published synthesis of this unusual pyrrole are reviewed. The synthetic strategies used are analysed and compared with the biosynthesis.